The Effect Of Covid-19 Pandemic On Financial Performance Of Covid-19 Referral And Non-Referral Hospital - Lisamelia; Adi Wiratno (Enrichment : Journal of Management, 2022)
The purpose of this paper is twofold: to examine the relationship between Covid-19 pandemic and hospital performance and to compare the performance of Covid-19 referral and non-referral hospitals. To this end, secondary data were obtained from fourteen state-owned hospitals. These fourteen hospitals were parts of Indonesia Health Care Corporation (IHC). The data on hospital’s performance were used to represent the population of all state-owned hospitals in Indonesia. A correlation test was performed using the Rank Spearman test, while the comparison test was done using Mann-Whitney. Test results showed a weak, positive relationship between both types of hospitals in terms of ROA, a moderate, positive relationship between both types of hospitals in terms of EBITDA margin, and a moderate, negative relationship in terms of BOPO ratio. A significant difference in financial performance was also noticed between Covid-19 referral and non-referral hospitals. The result implies that hospitals play a central role in handling Covid-19 pandemic, especially those appointed as the referral hospital by the authority. Referral hospitals actively handled the pandemic, as indicated by the significant difference in financial performance compared to non-referral hospitals. This work is expected to contribute to future studies on similar topics and the hospital management's decision-making process when a similar condition occurs in the future.